Progress of natural sesquiterpenoids in the treatment of hepatocellular carcinoma - Wang, Xiaodong; Meng, Fancheng; Mao, Jingxin (Frontiers in Oncology, 2024)
Hepatocellular carcinoma is one of the common malignant tumors of digestive tract, which seriously threatens the life of patients due to its high incidence rate, strong invasion, metastasis, and prognosis. At present, the main methods for preventing and treating HCC include medication, surgery, and intervention, but patients frequently encounter with specific adverse reactions or side effects. Many Traditional Chinese medicine can improve liver function, reduce liver cancer recurrence and have unique advantages in the treatment of HCC because of their acting mode of multi-target, multipathway, multi-component, and multi-level. Sesquiterpenoids, a class of natural products which are widely present in nature and exhibit good anti-tumor activity, and many of them possess good potential for the treatment of HCC. This article reviewed the anti-tumor activities, natural resources, pharmacological mechanism of natural sesquiterpenoids against HCC, providing the theoretical basis for the prevention and treatment of HCC and a comprehensive understanding of their potential for development of new clinical drugs.